THE EFFECT OF APPLYING COOPERATIVE LEARNING MODEL ON STUDENT COMPETENCE IN NATURAL SCIENCE: LITERATURE STUDY ABOUT TWO STAY TWO STRAY WITH STUDENT WORKSHEET - Siska Purnama Sari; Ardi Ardi; Syamsurizal Syamsurizal; Ganda Hijrah Selaras (ATRIUM PENDIDIKAN BIOLOGI, 2021)
This writing is based on the results of observation and interview in SMP 3 Koto XI Tarusan which show the learning process still tends to be teacher-centered. Students are not seen actively, self-confidence in expressing ideas are still low. As a result, the level of understanding towards learning material still low and this also has an impact on students learning competencies in terms of attitudes, knowledge and skill. One way that can be used to demand the activeness of students is by applying a learning model. Based on the literature study, the writer found a suitable learning model to overcome the problems found, namely by applying the Two Stay Two Stray type of cooperative learning model accompanied by LKDP. This type of research is a literature study using descriptive analysis. The data used are secondary data, namely scinentific journals such as articles. The data analysis technique consists of several stages, namely the preparation, impelementation and completion stages. The procedure used in this study is to browse articles contained in online journals on Googele Scholar research, collect articles related to accredited or indexed criteria, review each selected articles, and draw conclusions from the review Each article.  Based on the literature study counducted, it can be seen that learning using the Two Stay Two Stray of cooperative learning model accompanied by LKPD can imporove the learning competence of studends.